The impact of earthworks on older trees in historical parks - Łukaszkiewicz, Jan; Fortuna-Antoszkiewicz, Beata; Borowski, Jacek (Journal of Environmental Engineering and Landscape Management, 2022)
The publication aims to investigate the quantitative impact of linear earthworks in urban parks, e.g. during roads’ and pavements’ modernization in the old trees’ root zones, on the increment in their external parameters (e.g. trunk circumference). Pilot studies (Warsaw, Poland) were carried out 2003–2019 in two historical parks: Ursynów and Królikarnia. The dataset of trees’ parameters is based on detailed dendrological inventories. Test groups consisted of trees exposed to damage and not exposed to damage (Ursynów) and the control group – trees growing in unchanged site conditions (Królikarnia). Among the three most abundant species of dendroflora, Norway maples (Acer platanoides L.) show the most visible difference (>1.8 cm) between the normal and the inhibited growth in trunk circumference. Two other species – black locusts (Robinia pseudoacacia L.) and small-leaved limes (Tilia cordata Mill.) – also revealed statistically significant differences in the increment of the trunk circumference (respectively: >1.3 cm and >1.4 cm). In general, the reaction of affected trees was a significant reduction of circumference increments from 2.6 to 4.0 times concerning trees not exposed to damage. The verification made with the resistograph in 2019 confirmed a statistically significant decrease in radial increments of trees remaining in the impact zone of the earthworks.